Digital forensics for legal professionals understanding digital evidence from the warrant to the courtroom - Daniel, Larry (Syngress, 2012)
Digital Forensics for Legal Professionals provides you with a guide to digital technology forensics in plain English. In the authors' years of experience in working with attorneys as digital forensics experts, common questions arise again and again: "What do I ask for?" "Is the evidence relevant?" "What does this item in the forensic report mean?" "What should I ask the other expert?" "What should I ask you?" "Can you explain that to a jury?" This book answers many of those questions in clear language that is understandable by non-technical people. With many illustrations and diagrams that will be usable in court, they explain technical concepts such as unallocated space, forensic copies, timeline artifacts and metadata in simple terms that make these concepts accessible to both attorneys and juries. The authors also explain how to determine what evidence to ask for, evidence might be that could be discoverable, and the methods for getting to it including relevant subpoena and motion language. Additionally, this book provides an overview of the current state of digital forensics, the right way to select a qualified expert, what to expect from a qualified expert and how to properly use experts before and during trial. Includes a companion Web site with: courtroom illustrations, and examples of discovery motions Provides examples of direct and cross examination questions for digital evidence Contains a reference of definitions of digital forensic terms, relevant case law, and resources for the attorney
Includes bibliographical references and index. - Print version record
Keywords: Electronic discovery (Law) -- United States; Evidence, Documentary -- United States; Electronic records -- Law and legislation -- United States; Computer files -- Law and legislation -- United States; Communication électronique des pièces; États-Unis; Preuve littérale; États-Unis; Computer files; Law and legislation; Electronic discovery (Law); Electronic records; Law and legislation; Evidence, Documentary; United States